The new tsar : the rise and reign of Vladimir Putin - Myers, Steven Lee (Alfred A. Knopf, 2015)
"The epic tale of the rise to power of Russia's current president-- of his emergence from shrouded obscurity and deprivation to become one of the most consequential and complicated leaders in modern history. Former New York Times Moscow bureau chief Steven Lee Myers has followed Vladimir Putin's path for many years, and gives us the fullest, most absorbing account we have of his rise to power. This gripping narrative elucidates a cool and calculating man with enormous ambition and few scruples. We see Putin, a former KGB agent, come to office in 2000 as a reformer, cutting taxes, expanding property rights, bringing a measure of order and eventual prosperity to millions whose only experience of democracy in the early years following the Soviet collapse was instability, poverty, and criminality. But Myers makes clear how Putin then orchestrated a new authoritarianism, consolidating power, reasserting the country's might, brutally crushing revolts, and swiftly dispatching dissenters, even as he retained-- and continues to retain-- the support of many. As the world struggles to confront a newly assertive Russia, the importance of understanding Putin has never been greater. This keenly insightful, riveting book provides an essential key to that understanding"--